Assessment of proteinuria for early diagnosis and risk prediction of dengue hemorrhagic fever/dengue shock syndrome in dengue infections - DR.S.SAKTHI SELVA KUMAR,; DR.SURESH KANNA,; DR.S.PALANIANDAVAN, (International Journal of Pharma and Bio Sciences, 2017)
Dengue is the one of most important endemic disease in India which is getting more common in recent years, affecting all age groups. Following an initial febrile period, a small proportion of infected patients develop a vasculopathy, who have a risk for severe vascular leakage and shock. Since there is no treatment available, close clinical monitoring and careful fluid therapy is the only way of management for those with severe dengue disease, i.e., dengue haemorrhagic fever (DHF) or dengue shock syndrome (DSS). Differentiation between dengue and other common febrile illnesses is difficult during the early febrile phase, and risk prediction for development of shock is poor.The presence of proteinuria is recognized as a useful early predictor for subsequent complications in a number of other disorders with vascular involvement.Significant proteinuria occurs in dengue shock syndrome and it is possible that proteinuria in the early-phase may be helpful for identification of patients who are likely to develop severe complications in dengue. Predicting disease severity is important in triaging patients requiring hospital care. We aim to study the value of proteinuria in predicting the development of dengue haemorrhagic fever (DHF), utility of urine dipstick test as a rapid prognostic tool.We measured formal urine albumin to creatinine ratios (UACRs) in daily samples obtained from a large cohort of Patients with dengue infections confirmed in by dengue RT-PCR or NS1 antigen detectionrecruited at SBMCH. Dengue cases had median fever duration of 6 days at enrolment. DHF was diagnosed in cases according to the WHO 1997 guideline. Dengue fever (DF) patients were predominantly younger. Compared to DF, DHF cases had significantly higher peak urine protein creatinine ratio (UPCR) during clinical course (26 vs. 40 mg/mmol; p, 0.001). thus Proteinuria measured by a laboratory-based UPCR test may be sensitive and specific in prognosticating adult dengue patients.